Recent Innovations in Cloud Computing: Transforming the Digital Landscape - Sravanthi Gopala, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive technical article explores recent innovations and transformative developments in cloud computing, examining their impact on enterprise architecture and digital transformation. It investigates key areas including serverless computing evolution, edge computing integration, AI/ML infrastructure innovations, and security advancements. The article delves into how organizations are leveraging cloud technologies to enhance operational efficiency, improve scalability, and maintain robust security postures. It covers critical aspects such as zero-trust architecture implementation, MLOps practices, and environmental sustainability initiatives in cloud computing. Through examination of various architectural patterns, performance considerations, and emerging trends, the article highlights how cloud computing continues to evolve, particularly in areas of autonomous operations and sustainable computing practices. It also addresses crucial challenges and solutions in areas such as cold start optimization, resource management, and compliance automation, providing insights into how organizations can effectively navigate the complex landscape of modern cloud computing while preparing for future technological advances.
Keywords: Cloud Infrastructure Innovation; Edge Computing Integration; Serverless Architecture; MLOps Automation; Sustainable Cloud Computing